Exploring the anatomical and metabolomic variabilities in the seagrass Posidonia oceanica (L.) Delile fruits - Federico Pinna; Mauro Commisso; Flavia Guzzo; Simonetta Bagella; Giulia Ceccherelli; Giovanna Becca; Maria Franca Usai; Patrizia Stipcich (Marine Biology, 2026)
Anatomical and metabolomic variability in marine plants can provide valuable insights into species adaptive strategies and resilience to environmental changes. This study explores the anatomical characteristics and metabolomic profiles of Posidonia oceanica fruits, a key Mediterranean seagrass species, collected from three areas in Sardinia (Alghero, Oristano, and Olbia). Anatomical analyses of pericarps assessed cuticle thickness and intercellular spaces. Additionally, metabolomic analyses were performed using UPLC-HRMS on both the pericarps and the seeds. Significant differences in the percentage of intercellular spaces among pericarps from the different areas were found, with those from Alghero, exhibiting a higher percentage. Metabolomic analyses highlighted distinct profiles across areas, with Alghero pericarps showing greater metabolomics complexity, characterized by high levels of chicoric acid, hydroxycinnamate and hydroxybenzoate derivatives, while seeds exhibited an abundance of procyanidins, benzoic and caffeic acids and quercetins. Interestingly, seeds from Olbia presented a higher abundance of lipids. This study provides the first comprehensive metabolomic characterization of P. oceanica pericarps and seeds, highlighting significant variability that may influence seed dispersal, germination, and species adaptability. Our findings offer new perspectives for the conservation and management of this key species, which are particularly relevant in the context of global climate change.